2022
DOI: 10.1111/ajag.13158
|View full text |Cite
|
Sign up to set email alerts
|

Free public transport and older people: An ethnographic study of an Australian bus service

Abstract: Objectives This study explores older people's use of a free bus service in Wollongong, Australia. The research focus was on understanding the experiences of people over the age of 60 who use the service and the extent to which it contributes to their physical, mental and social well‐being. Methods The ethnographic research utilised fieldwork and interviews for data collection. Participant observations took place on the bus, and interviews were undertaken at bus stops. Data were analysed using an inductive them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Regarding the study design of included studies, Seventeen studies (25-41) used a qualitative cross-sectional design, six (11, 42-46) used quantitative cross-sectional design, three (47-49) were cross-sectional mixed methods, two (50,51) were longitudinal pre-post quantitative studies, two (52,53) used an explanatory descriptive approach, one (54) used a longitudinal mixed method, another one (55) used multimethod approach, and two (17,18) were systematic reviews (Supplementary Table S2). In terms of barriers or facilitators that influenced public transport use, eighteen studies (11, 17, 18, 25-27, 29, 33, 36-38, 40, 43, 46, 48-50, 54) reported both physical and social barriers and facilitators (e.g., lack of ramp or concerns with ramp angle and deployment, lack of training of drivers and other systems users on the needs of PWD, resulting in lack of respect, free pass, lower floor buses, mobility training for people with visual impairment and PWD/age-awareness training for bus drivers), two (31,55) reported physical barriers (e.g., winter, ice, snow) and personal factors (e.g., fear of injury, lack of knowledge, or self-efficacy), two (11, 35) described only physical barriers, four (30,39,42,45) reported physical and social barriers and facilitators along with influencing personal factors (e.g., fear of being harassed inside the crowded buses, lack of knowledge of the public transport system), six (29,33,45,46,52,53) described user satisfaction only, and one (51) described self-efficacy (Supplementary Table S2). Specific details of all barriers, facilitators and influencing factors are presented in Supplementary Table S2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the study design of included studies, Seventeen studies (25-41) used a qualitative cross-sectional design, six (11, 42-46) used quantitative cross-sectional design, three (47-49) were cross-sectional mixed methods, two (50,51) were longitudinal pre-post quantitative studies, two (52,53) used an explanatory descriptive approach, one (54) used a longitudinal mixed method, another one (55) used multimethod approach, and two (17,18) were systematic reviews (Supplementary Table S2). In terms of barriers or facilitators that influenced public transport use, eighteen studies (11, 17, 18, 25-27, 29, 33, 36-38, 40, 43, 46, 48-50, 54) reported both physical and social barriers and facilitators (e.g., lack of ramp or concerns with ramp angle and deployment, lack of training of drivers and other systems users on the needs of PWD, resulting in lack of respect, free pass, lower floor buses, mobility training for people with visual impairment and PWD/age-awareness training for bus drivers), two (31,55) reported physical barriers (e.g., winter, ice, snow) and personal factors (e.g., fear of injury, lack of knowledge, or self-efficacy), two (11, 35) described only physical barriers, four (30,39,42,45) reported physical and social barriers and facilitators along with influencing personal factors (e.g., fear of being harassed inside the crowded buses, lack of knowledge of the public transport system), six (29,33,45,46,52,53) described user satisfaction only, and one (51) described self-efficacy (Supplementary Table S2). Specific details of all barriers, facilitators and influencing factors are presented in Supplementary Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…It is the most important factor to consider when travelling to or from stop or station for at least two reasons: walking is the primary access mode for trips from home to public transit and walking distance has a significant impact on public transport use (57). And this seems all the more plausible given that of the fifteen studies that have reported on the physical barriers that occur when walking to or from a bus stop/station, eight (26,28,32,33,36,44,47,50) have identified walking distance as a barrier to using public transport. Travelling to or from stop/station must be understood as an integral part of the travel chain, during which barriers may emerge and limit access to and use of public transit by PWD.…”
Section: Discussionmentioning
confidence: 99%
“…[19,20]. The sustainability of the public services system is reflected in the increase in educational resources [21], the optimization of traffic conditions [22,23], the health care system [24], the cultural level of the area [25], the consolidation of social security functions [26], and the improvement in digital services capacity [27]. The contribution of population and public services systems in regional systems shows that the former provides dynamic support for the sustainable development of regional systems, while the latter provides a process guarantee for the sustainable development of regional systems [28].…”
Section: Introductionmentioning
confidence: 99%